KEY APPROACHES TO THE DOCTRINE OF LONG-TERM DEVELOPMENT OF UKRAINE - L. Shynkaruk; I. Baranovska; L. Milman (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The approaches to the doctrine of long-term development of Ukraine, considering realities of functioning national economy, are substantiated. It is proposed diversification of Ukraine's economy to realize by two directions: through the modernization of traditional sectors and infrastructure and active transition to knowledge-intensive non-raw sectors of production and services. Directions institutional reforms with orientation on rapid improvement of the business environment and attract investment are determined. The basic directions of industrial policy, framework conditions of stimulation industry restructuring and priorities for SME development in Ukraine are defined.